The Role of Chest X-Ray in Intensive Care Unit - Mayson Ahmed Wanasi Khair; Shouq Mohammed Alamri; Ahlam Hameed Alrashidi; Malak Abdulrahman Lharbi; Yosra Saleh Al-moghamsi; Mashaeel Musallam Alharbi (International Journal of Innovative Research in Medical Science, 2021)
Purpose: Chest X-rays (CXRs) are the most common radiological tests performed in the intensive care unit (ICU). The purpose of the current study was to investigate the relationship between the performance CRX in ICU and the patient’s confirmed pathologic finding. Methods: This retrospective study was evaluated 50 ICU chest X-rays were retrieved from the Picture Archiving and Communication System (PACS) of the different Saudi Hospitals in Al-Medina (February - April 2017). Frequency Distribution, Ratio and Linear Regression were used for statistical analysis. Result: This study demonstrated that based on analyzing the data, 92% of chest X-ray requests were used among 50 ICU patients to confirm the diagnosis, and a significant relationship was found between the use of chest X-rays between the ICU patients and the patient's confirmed pathologic finding which may mean that chest X-ray had a great role in confirming the disease or its complications. There has been a recommendation to perform daily CRX for patients with severe cardiopulmonary disease or receiving mechanical ventilation, as well as immediate CXR imaging for all patients who have had endotracheal tubes, feeding tubes, vascular catheters, and chest tubes. The most effective principle of radiation protection is distance, when performing an X-ray, the technologist must be at least six feet (1.5 to 2 m) from the radiation source. If the technician needs to be close to the radiation source, wearable lead shields and thyroid collars can protect the radiation-sensitive areas of the body. Conclusion: The chest X-ray of ICU patients was an important diagnostic tool that would affect patient management; however, it may also be a tool that can lead to serious complications for patient. A small sample size was used in this investigation that results in unconfirmed information, the future research using a large sample size is needed to carry out a more reliable and valid information.